Development and Characterization of Edible Coating Potato Peel Starch (Solanum tuberosum L.) and Sungkai Leaves Extract to Prolong the Shelf Life of Strawberries (Fragaria sp.) - Ardiani, Ajeng Putri; Yefrida, Yefrida; Refilda, Refilda (Universitas Gadjah Mada, 2025)
This study developed and characterized edible coatings from potato peel starch (Solanum tuberosum L.) to prolong the shelf life of strawberries (Fragaria sp.). Due to its high starch content, the edible coating was formulated using potato peel starch as the base material, and Sungkai leaf extract was added to enhance its antioxidant properties. The coating was characterized by viscosity, pH, color, antioxidant content, and thickness; and analyzed using FTIR, XRD, and SEM. The coating was applied to strawberries, and its effectiveness was evaluated based on weight loss and decay rate during storage. The edible coating was characterized by lower viscosity (10 cP), lower pH (6.83), darker color indicating bioactive compounds, and higher antioxidant content (5.72 mg AAE/g). FTIR data confirmed physical interactions among components; XRD revealed a semi-crystalline structure; and SEM showed a porous surface with visible cracks. Application of strawberries reduced weight loss and decay by 22.88 and 1.33% (day 4 at 3–5 °C) and 46.1 and 2.67% (day 12 at 28–31 °C). These results demonstrate the potential of potato peel starch and Sungkai leaf extract as an eco-friendly preservation solution.